Associations of friendship and children's physical activity during and outside of school: A social network study - Jodie A. Stearns; Jenny Godley; Paul J. Veugelers; John Paul Ekwaru; Kerry Bastian; Biao Wu; John C. Spence (Elsevier, 2019)
Friendships play a significant role in child development and may influence children's physical activity (PA). Using a whole-network approach, this study examined whether school-based friends are more similar in their pedometer-measured PA compared to children who are not friends, and whether these patterns vary by gender, strength of friendship (best vs. close friends), and during vs. outside of school. The analytical sample included 706 grade 5 students (10- to 11-years-old) in 27 schools who were participating in the APPLE Schools project (Alberta Project Promoting healthy Living for Everyone in schools) in Edmonton and Fort McMurray, Alberta, Canada in the spring of 2013. Data collected included student and parent survey responses, time-stamped pedometer data for nine consecutive days, and close and best within-school and within-grade friendship nominations. We used Multiple Regression - Quadratic Assignment Procedure (MR-QAP) to examine the effect of friendship ties on PA similarity overall, and for during and outside of school periods, controlling for covariates and clustering within schools. When all friendships (i.e., close and best) were considered, female friends exhibited more similar levels of overall PA than non-friends, and these findings held for school days, the during-school period, and non-school days. When close and best friends were examined separately in the same model (non-friends as the referent), both close and best friends were more similar than non-friends. The close friendship findings held for non-school days, and the best friendship findings held for school days, including the during-school and before- and after-school periods. For males, only reciprocated best friends had more similar levels of overall PA compared to unreiprocated friendships and non-friends. Programs and policies that focus on increasing PA in children may benefit from incorporating friendship-based strategies and programming, especially for females. Keywords: Social network analysis, Friendships, Physical activity, Children, Pedometers